PENGARUH PEMBERIAN INFORMASI OBAT TERHADAP TINGKAT KEPATUHAN PENGGUNAAN ANTIBIOTIKA PADA PASIEN ISPA DI PUSKESMAS KOTAGEDE I YOGYAKARTA - Muljabar, Stefy Muliyani; Supadmi, Woro (Universitas Ahmad Dahlan, 2014)
ARI is an acute respiratory infection requiring antibiotics. The use of antibiotics shouldbe routinely to prevent resistance. The design of this research was experimental by treatment ofthe cases. How to collect the data used prospective method. The subjects of research who fulfilthe inclusion criteria were 44 patients with acute respiratory infection were divided into twogroups: 22 patients who were given information as the treatment group and 22 patients whowere not given information as the control group. Data was collected through interview to knowthe rest of the drug and questionnaires filling compliance with Modification Morisky AdherenceScale (MMAS). The pattern for antibiotic used in patients of acute respiratory infection atcommunity health centre Kotagede I Yogyakarta were Amoxicillin (65.9%), Cotrimoksazol (25%), Erithromycin (6.8%), and Ciprofloxacin (2.3%). The level of patients compliance byquestionnaire MMAS was 59.09% high compliance, and 40.91 % low compliance. The level ofpatients compliance by the rest of drug was 86.36% and patients uncompliance was 11.36%.The results of questionnaire MMAS with the Chi-Square test p=0.220 (p>0.05), this shows thatgiving drug informations had no influence to level compliance for antibiotic used in patiens ofacute respiratory infection at Community Health Centre Kotagede I Yogyakarta.